2012
DOI: 10.1007/s00449-012-0761-x
|View full text |Cite
|
Sign up to set email alerts
|

Process optimization of xylanase production using cheap solid substrate by Trichoderma reesei SAF3 and study on the alteration of behavioral properties of enzyme obtained from SSF and SmF

Abstract: This study aimed to assess the variability in respect of titer and properties of xylanase from Trichoderma reesei SAF3 under both solid-state and submerged fermentation. SSF was initially optimized with different agro-residues and among them wheat bran was found to be the best substrate that favored maximum xylanase production of 219 U (gws)(-1) at 96 h of incubation. The mycelial stage of the fungi and intracellular accumulation of Ca(++) and Mg(++) induced maximum enzyme synthesis. Inoculum level of 10 × 10(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 30 publications
0
35
0
3
Order By: Relevance
“…It has also been shown that sterilized WB induced higher ␤-glucosidase activity for A. saccharolyticus compared to pretreated corn stover [56]. In several cases WB has been reported as the substrate that yields the highest enzyme activities of both xylanases and cellulases for many ascomycetes, compared to other lignocellulosic wastes [66][67][68][69]. For instance, A. niger (BC-1) grown on WB in solid state settings had an endoglucanase activity of 48.22 U/gs, which was the highest by a margin of 6.36 U/gs compared to other substrates.…”
Section: Medium Composition For Enzyme Productionmentioning
confidence: 99%
“…It has also been shown that sterilized WB induced higher ␤-glucosidase activity for A. saccharolyticus compared to pretreated corn stover [56]. In several cases WB has been reported as the substrate that yields the highest enzyme activities of both xylanases and cellulases for many ascomycetes, compared to other lignocellulosic wastes [66][67][68][69]. For instance, A. niger (BC-1) grown on WB in solid state settings had an endoglucanase activity of 48.22 U/gs, which was the highest by a margin of 6.36 U/gs compared to other substrates.…”
Section: Medium Composition For Enzyme Productionmentioning
confidence: 99%
“…Therefore, an additional important characteristic of (hemi) cellulolytic enzymes is that they should be stable in the presence of the phenolic compounds that can cause enzyme inhibition and deactivation [23,24]. Previous studies have reported differences in the characteristics of enzymes produced using SSF and SmF, in terms of optimal pH and temperature, thermal stability, kinetic parameters, and size [39,40]. The present work adds to this knowledge by demonstrating that the endoglucanases and ␤-glucosidases produced under SSF were less prone to deactivation by the phenolics in the medium, since greater thermostability was observed in the presence of higher concentrations of these compounds.…”
Section: Influence Of the Type Of Cultivation System On Enzyme Thermomentioning
confidence: 99%
“…Soya oil cake was observed to be the best substrate for xylanase production. Various other agro-residues such rice bran, coconut coir pith, dry banana leaves, tea exhausts (Kar et al, 2013), cantaloupe, orange peel, banana peel, watermelon rinds (Mohammed et al, 2013) and Jatropha curcas seed-cake (Ncube et al, 2012) have been investigated as substrates for enzyme production.…”
Section: Effect Of Different Substrates and Nitrogen Source On Xylanamentioning
confidence: 99%